Collaborative Leadership In Education Management: Building Effective Learning Communities In Islamic Institutions - Nur Efendi (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study investigates the role of collaborative leadership in building effective learning communities within an Islamic educational institution, focusing on SMKN Tulungagung. The research addresses three main aspects: how collaborative leadership shapes educational management practices, how it supports the development of learning communities, and how both elements interact within the institutional context. A qualitative case study design was employed to capture in-depth perspectives from the principal, teachers, and administrative staff. Data were collected through semi-structured interviews, observations, and document analysis, followed by thematic analysis. The findings reveal that collaborative leadership fosters shared decision-making, open communication, and collective responsibility, which strengthen coordination and accountability in educational management. Learning communities are developed through structured collaboration, professional dialogue, and reflective practice, contributing to improved instructional quality and teacher engagement. The study also identifies a dynamic interaction in which leadership enables collaboration, learning communities enhance instructional practices, and feedback from outcomes informs leadership strategies. These findings indicate that collaborative leadership is essential in sustaining effective learning communities and improving institutional performance in Islamic educational settings.